Variable sea‐ice conditions influence trophic dynamics in an Arctic community of marine top predators. Issue 13 (30th May 2019) - Pratte, Isabeau; Braune, Birgit M.; Hobson, Keith A.; Mallory, Mark L.
Abstract: Sea‐ice coverage is a key abiotic driver of annual environmental conditions in Arctic marine ecosystems and could be a major factor affecting seabird trophic dynamics. Using stable isotope ratios of carbon (δ 13 C) and nitrogen (δ 15 N) in eggs of thick‐billed murres ( Uria lomvia ), northern fulmars ( Fulmarus glacialis ), glaucous gulls ( Larus hyperboreus ), and black‐legged kittiwakes ( Rissa tridactyla ), we investigated the trophic ecology of prebreeding seabirds nesting at Prince Leopold Island, Nunavut, and its relationship with sea‐ice conditions. The seabird community of Prince Leopold Island had a broader isotopic niche during lower sea‐ice conditions, thus having a more divergent diet, while the opposite was observed during years with more extensive sea‐ice conditions. Species' trophic position was influenced by sea ice; in years of lower sea‐ice concentration, gulls and kittiwakes foraged at higher trophic levels while the opposite was observed for murres and fulmars. For murres and fulmars over a longer time series, there was no evidence of the effect of sea‐ice concentration on species' isotopic niche. Results suggest a high degree of adaptation in populations of high Arctic species that cope with harsh and unpredictable conditions. Such different responses of the community isotopic niche also show that the effect of variable sea‐ice conditions, despite being subtle at the species level, might have larger implications when considering the trophic ecology of the larger seabird community. Species‐specific responses in foraging patterns, in particular trophic position in relation to sea ice, are critical to understanding effects of ecosystem change predicted for a changing climate. Abstract : We investigated influence of sea ice on the trophic dynamics among four species of marine top predators. Despite being subtle at the species level, effect of sea‐ice conditions on isotopic niche and trophic position might have larger implication when considering the trophic ecology of the seabird community.